Implementasi Kontrol PID Pada Alat Negative Pressure Wound Therapy - Naufal Adkha; Eka Nuryanto Budisusila (Elkom: Jurnal Elektronika dan Komputer, 2026)
This study aims to implement Proportional-Integral-Derivative (PID) control in a Negative Pressure Wound Therapy (NPWT) device to improve the precision and stability of negative pressure applied to wounds. NPWT is a standard therapy for complex wounds that applies subatmospheric pressure to accelerate healing. The developed system consists of three operating modes, namely continuous, intermittent, and dynamic, to tailor therapy based on wound type and patient needs. The prototype was built using main components including the XGZP101DB1R pressure sensor, ESP32 microcontroller, DC vacuum motor, and LCD Nextion interface. The PID algorithm was optimized through a trial-and-error method to achieve a stable response with minimal overshoot and fast response time. Test results show that the system can operate in a pressure range of -25 mmHg to -150 mmHg with very high accuracy, as indicated by an error percentage below 2% across all modes. PID control proved effective in maintaining pressure according to the setpoint, with a response time ranging from 12.8 to 15.8 seconds depending on the target pressure. Thus, this research successfully developed a precise, stable, and adaptive NPWT system, ready for further testing in clinical applications.